Lattice boltzmann modelling of microchannel flow - Che Sidik, Nor Azwadi (Faculty of Mechanical Engineering, UTM, 2009)
A lattice Boltzmann algorithm to model the fluid flow in microchannel is developed. The details in determining the parameters critical for lattice Boltzmann application in microchannel flow are provided. The results from a 9-bit square lattice Boltzmann model are in good agreement with recent analytical data for a pressure-driven microchannel flow in slip flow regime. The differences between the predicted and the analytical for pressure gradients along the channel are well comparable. Results suggest that the lattice Boltzmann model described here is an effective computational tool for predicting more complex microfluidic systems that might be problematic using conventional methods.